Bridging Science and Hope: integrating and Communicating Lived experience in Accelerating Medicines Partnership® Schizophrenia Program - Ameneh Asgari-Targhi; Beier Yao; Lisa Brown; Suzanne Garcia; Arundati Nagendra; Kota Chin; Tashrif Billah; Nora Penzel; Omar John; Nicholas Prunier; Simone Veale; Elana Kotler; et al. (Schizophrenia)
Abstract The Accelerating Medicines Partnership Schizophrenia (AMP® SCZ) program integrates lived experience into psychosis research, leveraging over three decades of foundational studies to improve research quality, promote community engagement, and ensure ethical implementation of precision psychiatry. Lived experience is embedded in the program’s governance, shaping study protocols, recruitment strategies, and digital tools such as the mindLAMP platform. Study sites also integrate lived experience through youth advisory boards, peer support specialists, and advisory committees, ensuring diverse perspectives inform research design and implementation. These efforts aim to develop predictive tools and therapeutic strategies while maintaining ethical and participant-centered practices. Advocacy organizations, such as the National Alliance on Mental Illness (NAMI), have fostered collaboration among government, industry, and academic partners, shaping outreach and engagement strategies. Dissemination efforts, led by the Website and Outreach Workgroup (WOW), include an accessible, Section 508-compliant website and co-designed resources, building trust and engagement within communities. By integrating lived experience at every stage, the program aims to foster trust, enhance research outcomes, and inform future strategies for treatment and prevention. Watch Dr. Tina Kapur, Dr. Kathryn Eve Lewandowski, and Dr. Carlos A. Larrauri discuss this article and their work at: https://vimeo.com/1050068801 .